The Incident of Diarrhea among Cervical Cancer Patients Post Chemoterapy Treatment - ni ketut alit armini; Masfin Muhayanah; Aria Nastiti (Universitas Airlangga, 2016)
Backgrounds : Cervical cancer is second most diseases suffered by women. Chemotherapy is primary treatment for cervical cancer. Chemotherpy has some side effect, and one of them is diarrhea. Diarrhea make cervical cancer suffered more. The purpose of this research was to analyze the correlation of factor’s that cause diarrhea on cervical cancer.Methods : This research uses descriptive analitic method with retrospective design. The population in this research is all patients who had post first chemotherapy. Sample in this study were 21 respondents, with purposive sampling. Variable independent were type of chemotherapy drugs, character of chemotheraphy, staging, stress and dietary. Variable dependent was diarrhea. Data collected using quesionare. Data were analyzed using chi square test with level of significant α≤0,05.Results : The result of the study reveals that type of the chemotherapy drug p:0,598, character of chemotheraphy p:0,336,. Staging has correlation with diarrhea significant of p:0,022. Stress and dietary analysisis presented p:0,00. It means that there was significant correlation with diarrhea.Conclusion : It can be concluded that diarrhea incident related to staging, stress and dietarry. There‘s no correlation between type of chemotherapy drug, character of chemotheraphy with diarrhea Further studies should give health education about dietary causing diarrhea, chemotherapy procedural and sides effect’s, increase supports for patient with cervical cancer.